2020
DOI: 10.29069/forscience.2020v8n2.e707
|View full text |Cite
|
Sign up to set email alerts
|

A eficiência econômico-financeira de operadoras de planos de saúde: a influência da modalidade

Abstract: Diante de um grande mercado que movimenta milhões anualmente e atende a mais de 20% da população brasileira quanto à saúde, fazem-se necessários estudos relacionados à eficiência econômico-financeira das Operadoras de Planos de Saúde (OPS). Soma-se a isso o fato que o mercado de saúde suplementar vem diminuindo ao longo dos últimos 15 anos. Dessa maneira, o estudo dessa eficiência mostra-se importante para a manutenção dessas empresas no mercado. Uma das formas de se analisar a situação financeira dessas organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…Self-managing providers (SelfM), medical cooperatives (MCoop), and philanthropic entities (PhilaT) tend to have a higher IDSS than OPS operating in group medicine (base category), which was expected, as this category presented the lowest mean for the IDSS calculated in 2018. This result confirms the study by Xavier and Souza (2020), who concluded that the worst economic and financial indicators were found for the category of OPS in group medicine.…”
Section: Results and Analysessupporting
confidence: 91%
“…Self-managing providers (SelfM), medical cooperatives (MCoop), and philanthropic entities (PhilaT) tend to have a higher IDSS than OPS operating in group medicine (base category), which was expected, as this category presented the lowest mean for the IDSS calculated in 2018. This result confirms the study by Xavier and Souza (2020), who concluded that the worst economic and financial indicators were found for the category of OPS in group medicine.…”
Section: Results and Analysessupporting
confidence: 91%
“…The results of the analysis are similar to those Silva & Loebel (2016) registered for the period 2008 to 2012 not only in terms of profitability but also in terms current liquidity, indicating consistent performance over time. In regard to variability, the indicators demonstrate a reasonable degree of homogeneity, in alignment with the result presented by Xavier & Souza (2020) based on information for the period 2010 to 2015. The explanation for the homogeneity of the indicators could be attributable to the regulated environment, especially in terms of the products and consumers' rights (Malta et al, 2004).…”
Section: Discussion Of the Resultssupporting
confidence: 83%